TECHNOLOGY-BASED EDUCATION MANAGEMENT IN SALAF ISLAMIC BOARDING SCHOOLS - Niswah, Sa'adatun; Asiyah, Nur; Nasikhin, Nasikhin; Wahyudi, Wahyudi (STAI Ma'had Aly Al-Hikam Malang, 2024)
This research aims to explore how salaf pesantren that are thick with traditional nuances can manage educational technology in their environment. This qualitative research with a case study approach involves in-depth observation and interviews with kyai, pesantren administrators, teachers, and students as an important part of collecting data which is then analyzed using the Miles and Huberman model. Research conducted at the Al Fadhlu salaf Islamic boarding school, Brangsong District, Kendal Regency, shows that in managing the use of technology, pesantren packages it into online and offline learning forms. Online technology is implemented through the use of social media such as YouTube, Facebook, and Instagram as da'wah media, while offline technology management relies on simple technology such as the use of PowerPoint in learning and laptops as a means of correspondence. In the aspect of curriculum management, the findings of this study show that pesantren have developed effective strategies for technology implementation, such as providing information technology subjects to students. This finding rejects the assumption that salaf pesantren only rely on traditional learning, on the contrary, proving that even though it seems traditional, salaf pesantren still adopts and teaches technology to its students. This research makes a significant contribution by showing that the use of technology can update education in salaf Islamic boarding schools, combining traditional values with technological advances to improve the overall quality of education.